Analisis Pengaruh Advertising, Personal Selling, Sales Promotion, Publicity dan Word of mouth terhadap Keputusan Pembelian - Robot, Juwita Mariska (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
This research is aimed to analyze the influence of Advertising, Personal selling, Sales Promotion, Publicity and Word-of-mouth on Purchase Decision of Precious Metals at PT. Pegadaian (Persero) South Manado Branch. This is an associative type of research using a judgment sampling approach and the multiple linear regressions as the tools of analysis. 100 respondents were used as samples, with the hypothesis testing of F and t-tests, where data were analyzed using SPSS 21.0. The findings show that Advertising and Personal Selling do not have significant effect on Purchase Decision, while Sales Promotion, Publicity, and Word-of-mouth have significant influence on Purchase Decision. Keywords: Advertising, Personal selling, Sales Promotion, Publicity, Word-of-mouth